PERENCANAAN LANSKAP KAWASAN WISATA PESISIR LALONG KOTA LUWUK, SULAWESI TENGAH - Debora Budiyono; Siti Nurisjah; Luky Adrianto (http://arl.faperta.ipb.ac.id/, 2013)
ABSTRACTLuwuk City is a coastal city that have resources variety both natural and man-made which can be developed into tourism area. One of the tourist resources in Luwuk City is bay or Lalong of Luwuk City, Central Sulawesi. The urban growth and population growth of Luwuk City tend to cause negative effect of Lalong of Luwuk City condition. Therefore, it takes efforts of landscape planning of coastal tourism area which can improve physical environment, increase society and government budget revenues, and promote environmental awareness to Lalong Luwuk City society. The study purpose is to plan the landscape of Lalong Luwuk City as the coastal tourism areas to be a sustainable coastal tourism area by identifying and analyzing ecological condition of coastal area, potential objects, attractions and coastal area view to support a tourism attraction, local communities, government and private participation to support coastal area sustainability. The study used quantitative descriptive method. The analysis method that used was ecological analysis to determine the sensitivity of coastal area, potential objects and attractions analysis by using questionnaires, and visual quality analysis by using scenic beauty estimation (SBE) to determine coastal tourism attractiveness, urban social analysis by using focus group discussion (FGD) to determine local support, and stakeholder preferences analysis by using analysis hierarchy process (AHP) to determine landscape plan model of coastal tourism area in Lalong of Luwuk City. The results showed that coastal area in Lalong of Luwuk City is potential enough for coastal tourism development. The coastal tourist development zone is classified into high classification area of 170 ha (7.30%), medium classification area of 2113.38 ha (90.67%), and low classification area of 47.29 ha (2.03%). Coastal tourism area planning in Lalong Luwuk City based on the concept of creating sustainable coastal tourism area. The concept goal is to protect natural and cultural resources and to improve local communities walfare. The development zone and coastal tourism planning were adapted from landscape characteristic that centered on tourism area by potential and potential enough classification. The concept implementation of landscape is dvelopment planning model which interpreted in three landscape units are natural landscape, seminatural landscape, and man-made landscape. Natural landscape development zone located in Tontouan Village, Mangkio Baru Village, and Kaleke Village. Seminatural landscape development zone located in Keraton Village, Luwuk Village, and Bungin Village. Man-made landscape development zone located in Soho Village and Baru Village.